(untitled) (Research, Society and Development, 2024)
Youth entrepreneurship has become a central topic in discussions about innovations, and economic development in recent decades. This transformation reflects not only the growing role of young people in leading innovative initiatives, but also the response to a global context marked by market volatility, technological acceleration, and the need to adapt to constantly changing demands. This article aims to present a study that analyzes the main challenges faced by young entrepreneurs, identifying strategies to overcome them and highlighting the role of technological tools in this process. The research addresses the evolution of the profile of young entrepreneurs, analyzing how cultural changes and digital transformation have shaped new opportunities and challenges. Based on a bibliographic study and the analysis of relevant cases, the article investigates the factors influencing youth entrepreneurship success, including the critical role of digital technologies, support networks, and public policies. Furthermore, it discusses how institutional mechanisms, such as incubators, financing systems, and mentoring programs, can mitigate structural barriers, promoting economic and social inclusion. By emphasizing the integration of innovation, strategy, and institutional support, this study offers a comprehensive perspective on the pathways to sustainability and the impact of youth entrepreneurship in the global context.